Sociodemographic and reproductive profile of women with abortion complications in hospital in Recife - Rosielle Costa de Brito; Ana Laura Carneiro Gomes Ferreira; Eduarda Carneiro Gomes Ferreira; Sylvia Marilia Aquino do Bu; Ariani Impieri de Souza (Universidade Federal do Rio de Janeiro, 2013)
To describe the sociodemographic and reproductive characteristics of women with abortion complications in a tertiary hospital in the city of Recife. A cross-sectional study retrospectively analyzed 569 medical records and found 122 with abortion complications in 2008 to 2010 at Instituto de Medicina Integral Prof. Fernando Figueira. The frequency of abortion complications was 21.4%. The majority of women were between 20 and 35 years old, had eight or more years of schooling, were from Recife and the Metropolitan area, had no previous history of abortion and half of them were married. Among the complications, there was a high frequency of infection (77.0%), followed by the need for blood transfusion (15.6%). It was concluded that women in this study were young, with good education, living in an urban area. The main complication was infection and this could have contributed to abortion complications in maternal morbidity and mortality rates.